A first trial to supplement local hardwood sawdust at the first soaking for the cultivation of Shiitake (Lentinula edodes) - Stephanie Nabhan; Soukayna Haidar Ahmad; Zeina El Sebaaly; Teodor Nedelin; Youssef Najib Sassine (PeerJ)
Supplementation of the growing substrate has been reported to enhance the production of cultivated mushrooms; however, supplementation using nano-sized additives is not yet investigated on Shiitake (Lentinula edodes). The study investigated the potential of a nano-supplement (Lithovit®-Amino25) containing an admixture of 25% L-amino acids on shiitake cultivated on sawdust from locally available oak, maple, and apple trees (oak sawdust: OS, maple sawdust: MS, and apple sawdust: AS). Initially, sawdusts were enriched equally with wheat bran (WB) and at the first soaking, Lithovit®-Amino25 was applied at 5 g/L. Treatments were: T1: OS-WB (control), T2: OS-WB+ nano-amino, T3: MS-WB, T4: MS-WB+ nano-amino, T5: AS-WB, and T6: AS-WB+ nano-amino. Among non-supplemented substrates, complete mycelia run, fruiting, and harvest dates were faster in T1 than in T3 and T5. Complete mycelial development was delayed by 7, 5, 9, and 6 d in T3, T4, T5, and T6 compared to T1. The harvest date was delayed by 7.7–8.3 d on maple sawdust and by 10.5–12.7 d on apple sawdust compared to oak sawdust. However, nano-supplementation hastened fruiting and harvest dates (by 9.3 d) in T4 compared to T3. The biological yield of the second harvest was higher on supplemented than on non-supplemented maple and apple sawdusts. Only T1 and T2 showed consistency in production over two consecutive harvests. Nano-supplementation improved the total biological yield in T2, T4, and T6 by 9.8, 21.0, and 22.5%, respectively. Nevertheless, all treatments, except T4, had lower biological efficiencies compared with T1. In T4, results of stepwise regression showed a strong positive correlation (R2 = 0.96) between the total biological yield and mushroom weight at the second harvest. Supplementation caused a slight or significant improvement in pileus diameter and mushroom firmness and a significant improvement in mushroom’s crude protein (by 2.9–8.2% compared to T1) and fiber contents (by 1–2.3% compared to T1). In conclusion, supplemented maple sawdust would alternate oak sawdust for shiitake production, though other timings of supplementation might be further investigated to optimize production on this substrate.